Biomimetic and Functional Nanomaterials for Molecular Imaging - Pedro Ramos-Cabrer; Jesús Ruiz-Cabello (MDPI AG, 2023)
Welcome to this Special Issue of the journal Pharmaceutics entitled "Biomimetic and Functional Nanomaterials for Molecular Imaging," which focuses on the exciting advancements in molecular imaging facilitated by biomaterials and nanotechnology [...]